An Analysis on Consumer Market of e-book in Japan - Masashi Ueda (International Telecommunications Society (ITS), 2017)
The e-book market in Japan is growing in this decade and according to Impress R&D this tendency will be continue. In this paper, we collected 3,000 samples by online survey and found a tendency of consumption of e-book in Japan by using conjoint analysis. We found 1) attachment to physical objects in Japanese consumers, 2) high MWTP for device and providers. We check this by other questions and found tendency of Japanese consumer for e-distribution services.
Keywords: 330; e-book; online contents market; consumer survey